Controlling corruption in India: Various approaches and their efficacy - Kapur, V.P. (2011)
Corruption is not a new phenomenon. What is alarming is the extent of the rot-both in its magnitude and its apparent all-pervasiveness-as also the highest levels of governance to which it has reached. Efficacy of the existing system, laws and procedures can have relevance for effective functioning/governance only if the political master have the will to act honestly; competent, honest and dedicated officers are placed in sensitive positions; allowed to act according to laws of the land and are made accountable for their actions.They have to be provided with the required manpower and infrastructure; and back-up of competent, honest and dedicated legal advisers and prosecutors, Who are not remote -controlled by some outside elements or amenable to extraneous influences. - Reprodeced.
Keywords: Corruption - India; Corruption